The stages of forming technology master’s professional and pedagogical competency in the process of professional preparation - Ящук, Сергій (Pedagogy of Higher and Secondary Education, 2014)
Yashchuk S. М. The stages of forming technology master’s professional and pedagogical competency in the process of professional preparation. The article deals with the stages of forming technology teacher’s professional and pedagogical competency and technique of teaching technologies. The author substantiates the processes of its formation and the results.